Composite Tissue Allotransplantation and Dysregulation in Tissue Repair and Regeneration: A Role for Mesenchymal Stem Cells - Antony, Anuja K.; Rodby, Katherine; O'Connor, Megan I.; Tobin, Matthew K.; Pearl, Russell K.; DiPietro, Luisa A.; Breidenbach, Warren C. (Frontiers in Immunology, 2013)
Vascularized composite tissue allotransplantation is a rapidly evolving area that has brought technological advances to the forefront of plastic surgery, hand surgery, and transplant biology. Composite tissue allografts (CTAs) may have profound functional, esthetic, and psychological benefits, but carry with them the risks of life-long immunosuppression and the inadequate abilities to monitor and prevent rejection. Allografts may suffer from additional insults further weakening their overall benefits. Changes in local blood flow, lack of fully restored neurologic function, infection, inflammation with subsequent dysregulated regenerative activity, and paucity of appropriate growth factors may all be involved in reducing the potential of CTAs and therefore serve as new therapeutic targets to improve outcomes. Strategies involving minimized immunosuppression and pro-regenerative therapy may provide a greater path to optimizing long-term CTA function. One such strategy may include mesenchymal stem cells (MSCs), which can provide unique anti-inflammatory and pro-regenerative effects. Insights gained from new studies with MSCs on composite allografts, advances in tissue regeneration reported in other MSC-based clinical studies, as well as consideration of newly described capacities of MSCs, may provide new regenerative based strategies for the care of CTAs.